HUBUNGAN PAPARAN PORNOGRAFI TERHADAP PERILAKU SEKSUAL REMAJA DI SMA NEGERI 1 SUNGAI PINANG - Raden Surahmat; Mareta Akhriansyah; Nuriza Agustina (LPPM Universitas Abdurrab, 2023)
Abstract Sexual behavior problems that occur in adolescents if it is not addressed immediately then it is feared will bring many catastrophic impacts on the personal lives of adolescents, families, and the general public. The condition of adolescent sexual behavior is increasingly faced with exposure to pornography which until now continues to threaten with many easy access in various media. This study aims to examine the relationship between exposure to pornography and adolescent sexual behavior at SMAN 1 Sungai Pinang, Ogan Komering Ilir Regency. This research is a quantitative descriptive study with a cross sectional approach, by using a questionnaire on the respondent which amounted to 64 people who were students of SMAN 1 Sungai Pinang OKI. The results obtained 48 respondents (75.0%) not exposed to pornographic media, 48 people (75.0%) did not experience pornography exposure and most of them did not engage in sexual behavior as many as 55 people (85.9%). It was found that respondents who engage in sexual behavior and experience exposure to pornography as many as 6 people (37.5%), more when compared with respondents who engage in sexual behavior and do not experience pornography exposure as many as 3 people (6.3%). The results of the chi-square statistical test obtained value = 0.006 which means that there is a relationship between exposure to pornography and adolescent sexual behavior at SMAN 1 Sungai Pinang OKI so that researchers recommend the need for a religious basis, appropriate early education about sex, parental support, the environment and the need for supervision by each party. because if exposure to pornography continues to occur, it is feared will have an impact on sexual behavior that has not occurred properly and even deviant sexual behavior occurs. Keywords: Exposure to pornography, Adolescents, Sexual Behavior Abstrak Masalah perilaku seksual yang terjadi pada remaja jika tidak segera diatasi maka dikawatirkan akan membawa banyak dampak bencana dikehidupan pribadi remaja, keluarga, dan masyarakat umum. Kondisi Perilaku seksual remaja kian dihadapkan dengan adanya paparan pornografi yang sampai saat ini terus mengancam dengan kemudahan akses di berbagai media. Penelitian ini bertujuan untuk melihat hubungan antara paparan pornografi dan perilaku seksual remaja di SMAN 1 Sungai Pinang Kabupaten Ogan Komering Ilir. penelitian ini merupakan penelitian deskriptif kuantitatif dengan pendekatan cross sectional, dengan menggunakan kuisoner pada responden yang berjumlah 64 orang yang merupakan siswa/i SMAN 1 Sungai Pinang OKI. Hasil penelitian didapatkan 48 responden (75,0%) tidak terpapar media pornografi, 48 orang (75,0%) tidak mengalami paparan pornografi dan sebagian besar tidak melakukan perilaku seksual sebanyak 55 orang (85,9%). didapatkan responden yang melakukan perilaku seksual dan mengalami paparan pornografi sebanyak 6 orang (37,5%), lebih banyak jika dibandingkan dengan responden yang melakukan perilaku seksual dan tidak mengalami paparan pornografi yaitu sebanyak 3 orang (6,3%). Hasil uji statistik chi-square didapatkan ρ value = 0,006 yang berarti bahwa terdapat hubungan antara paparan pornografi dengan perilaku seksual remaja di SMAN 1 Sungai Pinang OKI sehingga peneliti meekomendasikan perlunya dasar agama, pendidikan tentang seks sejak dini sesuai, dukungan orang tua, lingkungan serta perlunya pengawasan oleh setiap pihak karena jika paparan pornografi terus terjadi maka dikhawatirkan akan berdampak pada perilaku seksual yang belum sewajarnya terjadi bahkan terjadi perilaku seks menyimpang. Kata kunci : Paparan pornografi, Remaja, Perilaku Seksual